Progress in the application of remote sensing for water quality and human health mapping in informal settlements of South Africa: A review - Oupa E. Malahlela; Mologadi C. Mothapo; Fhumulani I. Mathivha; Nokulunga Hlengwa (Scientific African)
Informal settlements in South Africa are a part of the urban landscape which is impossible to ignore due to their socio-economic contribution to the urban economies. However, the rapid expansion of these settlements exposes the population to various environmental hazards such as floods, pollution, and waterborne diseases and thus requires continuous monitoring. The use of remote sensing data has proved very effective for mapping water bodies, water quality, flood risk and water-borne diseases in parts of the world and in South Africa. This review highlights the extent to which remote sensing technology was used for mapping water quality in informal settlements, water-borne diseases, challenges and opportunities that the technology presents for future research. The results from this review revealed that there was a gradual increase in the number of studies conducted for mapping of water quality in South Africa since 1982, with a peak publication of 15 articles in 2020. We found no literature on the application of remote sensing in South African informal settlements in areas of water-borne and water-related disease mapping, such as schistosomiasis, yellow fever, typhoid fever, dysentery, and cholera, among other common water-borne and water-related diseases. Malaria was found to be the most common water related disease that has been studied through remote sensing in South Africa due to the disease burden that exists, and the efforts made towards disease eradication. In this review, the use of unmanned aerial vehicles (UAVs) and high-resolution remote sensing is recommended as an alternative to traditional water-borne and water-related diseases surveillance especially in developing countries.